2017
DOI: 10.1093/europace/eux247
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose of dabigatran for the prevention of thromboembolism with minimal bleeding risk in Korean patients with atrial fibrillation

Abstract: Although D150 and D110 had a comparable efficacy, only D110 lowered the risk of major bleeding in Korean AF patients compared with warfarin. Even the guideline-discordant use of dabigatran 110 mg demonstrated a similar efficacy and safety compared with D150. However, further prospective randomized trials are needed in order to comprehensively evaluate whether D150 or D110 is the optimal dosage in Asian patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…61 Regarding the optimal dose in Asians, a retrospective study to determine the optimal dose of dabigatran in Korean patients with NVAF suggested a fixed dose of 110 mg might be sufficient regardless of dose-reduction criteria based on the comparable efficacy and favorable safety of the 110-mg dose to 150-mg dose. 62 This finding in Korea is consistent with the observational study of realworld data in Taiwan that did not show a benefit of the 150-mg dose over the 110-mg dose. 63 Also, those results support the real-world clinical practice for dabigatran in Asia that the 110-mg dose is preferred because of a concern about bleeding risk in Asian patients with a higher dose.…”
Section: Dabigatransupporting
confidence: 87%
See 2 more Smart Citations
“…61 Regarding the optimal dose in Asians, a retrospective study to determine the optimal dose of dabigatran in Korean patients with NVAF suggested a fixed dose of 110 mg might be sufficient regardless of dose-reduction criteria based on the comparable efficacy and favorable safety of the 110-mg dose to 150-mg dose. 62 This finding in Korea is consistent with the observational study of realworld data in Taiwan that did not show a benefit of the 150-mg dose over the 110-mg dose. 63 Also, those results support the real-world clinical practice for dabigatran in Asia that the 110-mg dose is preferred because of a concern about bleeding risk in Asian patients with a higher dose.…”
Section: Dabigatransupporting
confidence: 87%
“…63 Also, those results support the real-world clinical practice for dabigatran in Asia that the 110-mg dose is preferred because of a concern about bleeding risk in Asian patients with a higher dose. 62,63 The recommendation for dabigatran dose reduction to 110 mg in fragile patients is supported by real-world clinical data as well as the RE-LY study. However, clinical data on the optimal dabigatran dose in Asian patients with NVAF are not sufficient.…”
Section: Dabigatranmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabigatran 110 mg was associated with lower risk of major bleeding (HR, 0.19 [0.07–0.55]). In this study, the number of patients in dabigatran 150 mg was 294 compared with 550 in dabigatran 110 mg group and 990 in warfarin group, which may undermine the safety profile of dabigatran 150 mg. 67) …”
Section: Effectiveness and Safety Of Oral Anticoagulation In Asian Pomentioning
confidence: 99%
“…Therefore, NOACs might be more attractive treatment options for Asian AF patients. Consequently, several large scale real-world studies of NOACs also support better efficacy and safety of NOACs compared to warfarin in Asian AF patients 714151617. Nonetheless, there have been few studies in Korean non-valvular AF patients.…”
Section: Introductionmentioning
confidence: 99%